2022
DOI: 10.1108/ilt-03-2022-0107
|View full text |Cite
|
Sign up to set email alerts
|

Braking-experimental study on the relationship between friction material type and brake disc temperature

Abstract: Purpose This study aims to clarify the relationship of friction material type and brake disc temperature through braking experiment. Design/methodology/approach The braking performances of resin materials (RM), semimetallic materials (SM) and copper-based powder metallurgy materials (PM) friction blocks mating with forged steel brake disc were examined based on TM-I-type reduced-scale inertial braking dynamometer. The brake disc surface temperature was recorded by infrared thermal camera during braking. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…According to the divisional method in the section "Distribution of temperature gradient on the disc surface," the thermal energy gradient factor C for each zone can be calculated according to equation (10). thermal energy gradient factor C decreases from 0.094 to 0.085 and 0.055, and witnesses at the radius of 100, 95, and 90 mm respectively, where all are in the corresponding transition zone from the interior non-friction zone to friction zone.…”
Section: Relationship Between Temperature Gradient and Thermal Energy...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the divisional method in the section "Distribution of temperature gradient on the disc surface," the thermal energy gradient factor C for each zone can be calculated according to equation (10). thermal energy gradient factor C decreases from 0.094 to 0.085 and 0.055, and witnesses at the radius of 100, 95, and 90 mm respectively, where all are in the corresponding transition zone from the interior non-friction zone to friction zone.…”
Section: Relationship Between Temperature Gradient and Thermal Energy...mentioning
confidence: 99%
“…3 On the micro-scale, the increase of temperature will lead to the change of material properties in the contact zone, which will affect the contact behavior between the asperity and the friction and wear process. 4 Therefore, extensive investigations have been conducted to clarify the factors that are relevant to the brake disc temperature field, such as brake disc material and structure, 58 brake pad material, 912 shape, 1315 and arrangement pattern. 1618 Results demonstrated that, the brake pad shape and arrangement pattern cause the difference of distribution of friction arc length and brake force, which affects significantly the thermal distribution on the disc.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the local contact state increases the concentration degree of brake force, leading to an increase in brake disc temperature, so the measured temperature is higher than the calculated temperatures at speeds of 60 and 80 km/h. Finally, in the experiment, the high-temperature wear debris left the rubbing interface and carried away partial heat energy, accounting for the decrease in the disc temperature (Chen et al , 2022). Unfortunately, wear is neglected in the simulation.…”
Section: Experimental Verification Of the Thermo-mechanical Couple Modelmentioning
confidence: 99%
“…in relation to emissions released as a result of friction, in many drives around the world that actuate the braking system, including brake disc-pad friction devices brake. An example may be the works in which the authors [4,5,16,23,24] investigate the influence of various friction materials on the brake disc during operation. Included are papers [6] that cover the effects of other factors, such as moisture and corrosion, on friction functions and different brake disc materials.…”
Section: Introductionmentioning
confidence: 99%